2021
DOI: 10.48550/arxiv.2104.08290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radio Line Properties of Axion Dark Matter Conversion in Neutron Stars

R. A. Battye,
B. Garbrecht,
J. I. McDonald
et al.

Abstract: Axions are well-motivated candidates for dark matter. Recently, much interest has focused on the detection of photons produced by the resonant conversion of axion dark matter in neutron star magnetospheres. Various groups have begun to obtain radio data to search for the signal, however, more work is needed to obtain a robust theory prediction for the corresponding radio lines. In this work we derive detailed properties for the signal, obtaining both the line shape and time-dependence. The principal physical e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…For instance, Ref. [26] has pointed out that the Doppler shift effects dominate the signal frequency broadening over the one from dark matter velocity dispersion. For the diluted axion star considered here, the axion particles in the initial axion star state are in a coherent BEC state.…”
Section: Radio Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ref. [26] has pointed out that the Doppler shift effects dominate the signal frequency broadening over the one from dark matter velocity dispersion. For the diluted axion star considered here, the axion particles in the initial axion star state are in a coherent BEC state.…”
Section: Radio Signalsmentioning
confidence: 99%
“…The resonant conversions of the axion particles for free axion particles and axion particles inside axion mini-clusters are discussed in Refs. [22][23][24][25][26] and [27,28], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Axions [1][2][3][4][5] represent one of the leading candidates for dark matter [6][7][8] and are predicted by a range of theories beyond the standard model [9,10]. One possibility to detect axions is via their astrophysical signatures, for instance via galactic halo axions decaying into two photons [11][12][13][14][15][16][17][18][19][20][21][22] or through observations of neutron stars [14,[23][24][25][26][27][28][29][30][31][32]. It is also of vital importance to complement these efforts through laboratory searches and there are a number of current and proposed experiments aiming to detect axion dark matter here on earth.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [18,19] has shown that this assumption is not sufficiently accurate to predict the signal due to the effects of the plasma and gravity which modify the ray tracing techniques first explored for straight line trajectories in [13]. These techniques allow calculation of the angular, frequency and time-dependence of the signal resulting from the propagation of photons through the magnetosphere.…”
mentioning
confidence: 99%